Clinical andrology and testosterone profile of Gir (Bos indicus) and Jafarabadi (Bubalus bubalis) bulls - SHELKE, VINAYA B; DHAMI, A J (The Indian Journal of Animal Reproduction, 2023)
Clinical andrological examination of Gir and Jafarabadi breeding bulls ( 4-7 yrs old) revealed normal external and internal genitalia with square to oblong scroti. The prepuce was much pendulous (8-12 inch) in Gir and tight in Jafarabadi bulls. Jafarabadi bulls had significantly lower scrotal circumference (33.03 ± 0.78 vs 37.39 ± 0.53 cm), scrotal volume (940.00 ± 21.10 vs 1217.50 ± 20.69 ml), libido score (2.34 ± 0.07 vs 2.90 ± 0.07) and plasma testosterone profile (0.68 ± 0.08 vs 7.56 ± 0.83 ng/ml) and longer reaction time (184.00 ± 28.79 vs 61.28 ± 16.92 sec) than the Gir bulls. Gir bulls of poor freezability group were significantly heavier and fatty with relatively lower scrotal measurements and testosterone profile, and longer reaction time. In Jafarabadi bulls, however, the scrotal length and reaction time were shorter in poor freezable than the good freezable group.